2021
DOI: 10.3390/diagnostics11081446
|View full text |Cite
|
Sign up to set email alerts
|

Automated Arrhythmia Detection Based on RR Intervals

Abstract: Abnormal heart rhythms, also known as arrhythmias, can be life-threatening. AFIB and AFL are examples of arrhythmia that affect a growing number of patients. This paper describes a method that can support clinicians during arrhythmia diagnosis. We propose a deep learning algorithm to discriminate AFIB, AFL, and NSR RR interval signals. The algorithm was designed with data from 4051 subjects. With 10-fold cross-validation, the algorithm achieved the following results: ACC = 99.98%, SEN = 100.00%, and SPE = 99.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…As a result of their studies, they obtained 98.96% accuracy in the teacher model and 98.13% accuracy in the student mode for seven rhythm classes. Faust et al [ 31 ] achieved 99.98% success in the SPNH dataset with the ResNet deep learning algorithm used by the authors in their study. Dhananjay et al [ 32 ] compared classical classification algorithms as well as their proposed model, the CatBoost model, in their study.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of their studies, they obtained 98.96% accuracy in the teacher model and 98.13% accuracy in the student mode for seven rhythm classes. Faust et al [ 31 ] achieved 99.98% success in the SPNH dataset with the ResNet deep learning algorithm used by the authors in their study. Dhananjay et al [ 32 ] compared classical classification algorithms as well as their proposed model, the CatBoost model, in their study.…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to structure a further study that used ECG signals obtained prior to identified AF episodes to provide insight into whether subtle differences can precede the onset of a PAF diagnosis. Since the SPAR attractor is independent of the heart rate, 21 it may also be helpful to incorporate complementary metrics that have been shown to be useful in the discrimination of AF episodes, such as R-R intervals 36 or features drawn from the Poincaré plots of heart rate differences. 37 Subtle changes in these metrics may also be distinguishable during normal sinus rhythm (distant from the actual AF episodes) and support the detection of the PAF diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used the PhysioNet public dataset and achieved 92.8% accuracy, but the ECG signal in 1D is considered classification. In [ 11 ], the authors calculated RR intervals to detect arrhythmia. The approach uses conventional methods and achieves an accuracy of 99.98%.…”
Section: Related Workmentioning
confidence: 99%